Surgical Treatment of Tardive Dystonia in Nepal: A Case Report - Shrestha, Resha; Taira, Takaomi; Shrestha, Pranaya; Rajbhanari, Pravesh; Dhakal, Sudan; Acharya, Samir; Pant, Basant (Nepal Journal of Neuroscience, 2016)
Tardive dystonia is a subtype of dystonia which is seen in patients receiving antipsychotic treatment for long period. Medical treatment of tardive dystonia is very complex and many cases do not respond well to currently available treatment and sometimes can be irreversible. Surgical treatments like pallidotomy and Deep Brain Stimulation (DBS) have shown some promising results. We report this case of Tardive Dystonia who benefitted from Pallidotomy. We believe this is the first case in Nepal. Nepal Journal of Neuroscience 12:81-84, 2015